2020
DOI: 10.3889/oamjms.2020.4276
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of the Engulfment and Cell Motility Protein-1 are Associated with Kidney Damage in Diabetic Nephropathy: A Single-Center Pilot Study in Indonesia Population

Abstract: BACKGROUND: Diabetic nephropathy (DN) is a chronic kidney disease with microvascular complications which influence a patient’s quality of life and poses a potentially significant economic burden. The discovery of new biomarkers is needed to gain a better understanding and find additional treatment approaches beyond controlling plasma glucose and blood pressure. The engulfment and cell motility protein called engulfment and cell motility protein (ELMO)-1 is known to play a role in tissue remodeling and is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The urine ACR in this study was calculated using random spot urine sampling. It is because a previous study reported that this sampling was more representative and practical in assessing albuminuria associated with complications of diabetes mellitus than a 24-hour urine sample (Elfiani et al, 2020). Albuminuria in patients with diabetes mellitus provides an early indication of kidney damage (Seidu, Barrat and Khunti, 2020).…”
Section: Baseline Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urine ACR in this study was calculated using random spot urine sampling. It is because a previous study reported that this sampling was more representative and practical in assessing albuminuria associated with complications of diabetes mellitus than a 24-hour urine sample (Elfiani et al, 2020). Albuminuria in patients with diabetes mellitus provides an early indication of kidney damage (Seidu, Barrat and Khunti, 2020).…”
Section: Baseline Subject Characteristicsmentioning
confidence: 99%
“…However, previous studies found that uncontrolled blood glucose levels or hyperglycemia were not significantly correlated with an increased risk of DN in individuals with T2DM https://doi.org/10. 33086/jhs.v15.i03.2681 Devy Afriyanti -The Role of Angiotensinogen rs699 in Diabetic Nephropathy Among Type 2 Diabetes Mellitus Patients with Uncontrolled Postprandial Glucose Levels (Elfiani et al, 2020). It certainly indicates the possibility of other risk factors more involved in developing DN, one of which is genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…5 The study in Malay Jambi ethnic reported similar result. 6 The new biomarker and genetic variant may play role in this event. Genetic factors are risk factors that cannot be modified, but early screening of these factors can provide information about the pathophysiology of DKD and promises hope for better treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%